Análisis del modelo de gobernanza del manejo pesquero en Chile: los Comités de Manejo - Carlos Tapia-Jopia (Nuevo mundo - Mundos Nuevos, 2022)
The modification of the Fisheries Law in Chile in 2013 incorporated changes to the fisheries governance model, through the creation of public-private instance, called Management Committe, where representatives of fishermen and public managers of fisheries participate. The model has appropiate characteristics. for análisis. On the one hand, the voting mechanism with differentiated weighting, to elect the representatives of the private sector in the committee, which generated distortions in the electoral process. On the other hand, consensus was established as the base mechanism for the committee's agreements. In this work, these measures and their impact on the operation of the management committees are analyzed.